Analisis Besaran dan Pembayaran Kapitasi Berbasis Komitmen Pelayanan terhadap Pengendalian Rujukan di Puskesmas Kota Bengkulu - Henni Febriawati; Yandrizal Yandrizal; Yulia Afriza; Bintang Agustina Pratiwi; Riska Yanuarti; Desri Suryani (Jurnal Kebijakan Kesehatan Indonesia, 2017)
Background: Puskesmas as primary health care center where the role of Puskesmas is interpreted as gate keeper or first contact and referral agent in accordance with standard of medical service. BPJS Kesehatan always strives to increase efficiency and effectiveness by developing quality control system of service and payment system of health service through capitation payment pattern to first  level health facility. Problem formulation, how the implementation of Kapuas basaran policy based on fulfillment of service commitment to control at Public Health Center of Bengkulu City. Research Objective, knowing the role of policy of capitation scale based on fulfillment of service commitment to referral control at public health center Bengkulu City. Research methods: This research uses quantitative and qualitative method with exploratory research design, unit of Puskesmas analysis in Bengkulu City. The type of this research is descriptive research to describe the implementation of capitation policy based on fulfillment of service commitment to referral number in public health center Bengkulu City. Results and discussion:Referral from public health center in Bengkulu City decreased from 2014 as many as 113,075 visits and 25,183 (22.27%) referrals, by 2015 149,483 visits and 26,963 (18.04%) referrals, 2016 226,313 visitation and 23,545 referrals (10 , 40%) In 2016 the number of participants in Bengkulu City was 156,854 inhabitants and the number of contact rate was 15.726 (10.06%). Visits were 13,068 (8.33%) and healthy visits 2,658 (1.69%). All informants understand about the activities undertaken to achieve the safe zone target ratio. Conclusions and recommendations:The implementation of a service commitment-based capitation policy can control the referral of the public health center. Informants have a common perception in achieving contact numbers to achieve the target of safe zones and achievement zones by optimizing public health efforts and individual health efforts to make healthy visits and sick visits to the community. Policy implementation can be developed by maximizing existing community health efforts in Puskesmas, improving the achievement of contact rates indicator, non-specialist referral ratios, and proline visits routinely.